Galectin 9 rescues the inducibility of IL-10 expression in regulatory B cells of patients with food allergy - Huang Huang; Minyao Li; Shuo Song; Shiyu Feng; Xiaoyang Feng; Yu Liu; Pingchang Yang; Pengyuan Zheng (Scientific Reports)
Abstract The deregulation of immune responses is what causes food allergy (FA) to occur. FA’s cause is still unknown. The goal of this study is to investigate the mechanism how the impaired production of IL-10 occurs in peripheral naive B cells of patients with FA. Samples from patients with FA and healthy controls (HC) were used to isolate CD19+ CD45R+ naive B cells from peripheral blood mononuclear cells (PBMC). Lipopolysaccharide (LPS) exposure was used to assess the expression of interleukin-10 (IL-10) in B cells. Although the FA and HC groups had similar total B cell counts, the FA patients had fewer IL-10+ B cell counts than the HC group. In peripheral B cells, the concentrations of IL-10 were inversely related to the concentrations of specific IgE, Th2 and Th1 cytokines in the serum. In patients with FA, peripheral B cells experienced impaired immune-suppressive functions. Galectin-9 could restore the defective induction of IL-10 expression in naive B cells of FA patients. In conclusion, FA patients with naive B cells experience impaired IL-10 induction. The induction of IL-10 in naive B cells of FA patients can be restored by galectin-9 treatment, which triggers B cells to differentiate into immune regulatory B cells.